Fatally flaky - Davidson, Diane Mott (William Morrow, 2009)
Colorado caterer Goldy Schulz encounters bridezilla--and murder--when bridezilla's fiancé is killed because he was doing research at the Gold Gulch Spa--an allegation that's confirmed when the deceased's best friend (Goldy's godfather) is attacked.